1996
DOI: 10.1101/gad.10.13.1608
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA export in response to stress in Saccharomyces cerevisiae.

Abstract: The response of eukaryotic cells to heat shock and other forms of stress occurs at both transcriptional and post-transcriptional levels. We used in situ hybridization to determine whether stress affected the subcellular distribution of poly(A]^ RNA in Saccharomyces cerevisiae. Following induction of stress by either heat shock (42°C) or addition of a high concentration of ethanol (10%), the nucleocytoplasmic export of most poly(A)^ RNA was blocked. In situ hybridization indicated that heat-inducible SSA4 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
185
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(206 citation statements)
references
References 68 publications
19
185
2
Order By: Relevance
“…This opens the possibility that, in vivo, the ATPase activity of Dbp5 could be modulated to regulate mRNA export. For example, it has been reported that during heat shock, bulk mRNA export is blocked and polyadenylated RNA accumulates inside the nucleus (39). Whether this is the result of decreased Dbp5 ATPase activity is unknown, but potential regulation of Dbp5 could occur through the modulation of InsP 6 levels or availability.…”
Section: Discussionmentioning
confidence: 99%
“…This opens the possibility that, in vivo, the ATPase activity of Dbp5 could be modulated to regulate mRNA export. For example, it has been reported that during heat shock, bulk mRNA export is blocked and polyadenylated RNA accumulates inside the nucleus (39). Whether this is the result of decreased Dbp5 ATPase activity is unknown, but potential regulation of Dbp5 could occur through the modulation of InsP 6 levels or availability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the repression of pre-mRNA splicing, exposure to severe heat shock stress at 42°C causes inhibition of mRNA export from the nucleus to the cytoplasm, which leads to accumulation of bulk poly (A) + RNA in the nuclei (Tani et al, 1995;Saavedra et al, 1996;Liu et al, 1996). Interestingly, it was shown that heat-shock inducible SSA1 and SSA4 mRNAs encoding heat shock proteins are exported to the cytoplasm under the same stressed conditions, indicating the presence of selective export pathways for heat shock mRNAs (Saavedra et al, 1996;Liu et al, 1996;Saavedra et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was shown that heat-shock inducible SSA1 and SSA4 mRNAs encoding heat shock proteins are exported to the cytoplasm under the same stressed conditions, indicating the presence of selective export pathways for heat shock mRNAs (Saavedra et al, 1996;Liu et al, 1996;Saavedra et al, 1997). The precise mechanisms for selective export of heat shock mRNAs are mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It appears to be mediated by nuclear export sequences present in RNA binding proteins such as HIV Rev (15). Poly(A) ϩ RNA export is dependent on the nucleotide state of Ran (10,16,17). Furthermore, binding of a heterodimeric protein complex is critical for export in the case of small nuclear RNAs, and this complex has recently been shown to interact with the ␣ subunit of importin (18,19).…”
mentioning
confidence: 99%